Statistical classification based on observations of random Gaussian fields - Šaltyte, J.; Dučinskas, K. (Mathematical Modelling and Analysis, 1999)
The problem of classification of objects located in domain D ⊂ R2 based on observations of random Gaussian fields with a factorized covariance function is considered. The first‐order asymptotic expansion for the expected error regret is presented. Obtained numerical results allow us to compare suggested expansion for some widely applicable models of spatial covariance function. Statistinis klasifikavimas remiantis atsitiktinių Gauso laikų stebėjimais Santrauka. Nagrinėjamas uždavinys apie objektų iš srities D C R 2 klasifikavimą, remiantis atsitiktinių Gauso laukų stebėjimais. Pateikti asimptotiniai laukiamos paklaidos įverčiai. Atlikus skaitinio modeliavimo eksperimentą naujasis skleidinys lyginamas su kitais žinomais skleidiniais. First Published Online: 14 Oct 2010